The relationship between workplace autonomy and the coworker helping and support on the workplace creativity among undergraduate interns in Malaysia - Cheong, Dickson; Goh, Zhao Han; Lim, Qing Kang (2022)
Workplace creativity is a key element that determine an organization to be successful in today’s era. However, it is unclear that the correlation between workplace autonomy and coworker support on workplace creativity. Therefore, this study utilized quantitative and cross-sectional design to examine the relationship between workplace autonomy and coworker support on workplace creativity among Malaysian undergraduate interns. There was a total of 85 respondents were recruited using purposive sampling by distributing the online survey through Facebook, WhatsApp, and Microsoft Teams. The participants recruited were mainly UTAR undergraduates who have completed their internship program. The result reported a significant positive correlation between workplace autonomy and coworker support on workplace creativity among Malaysian undergraduate interns through Pearson Correlation Coefficient. Besides, workplace autonomy and coworker support were found to significantly predict workplace creativity by performing multiple regression analysis. For future study, longitudinal study method is suggested to determine the causal-effect relationship between workplace autonomy, coworker support, and workplace creativity.